Pertahanan Jepang Pada Era Pasca Perang Dingin, Antara Nasionalisme Dan Konservatisme - Ani Khairunnisa (Universitas 17 Agustus 1945 Jakarta, 2017)
Defence and security are an important part of national policy. Japan that has been rise from its failure in the World War II and make various adjustments to the international security order. Despite reaping the pros and cons in international relations and get criticism will rise militarism of Japan. Japan has proven through increase the development of the domestic economy and continues to improve its positive image in foreign relations including defence and security policy. This papers will describe the condition.Key Words : Security, National Policy, Defence